Shear Strength of Frozen Grounds and Its Dependence on Texture - Pekarskaya,N. K. (1965)
Contents: Status of the problem. Initial premises for study of strength of frozen ground; Research methods; Experimental investigations of the resistance of frozen grounds to shear; Influence of temperature of frozen grounds on their strength; Strength of frozen grounds of different texture and ice content under rapid application of load; Strength of frozen grounds of different texture under the prolonged application of a load. Trans. of mono. Prochnost Merzlykh Gruntov pri Sdvige i ee Zavisimost ot Tekstury, Moscow, 1963 p3-108.